Quantitative microscopy of functional HIV post-entry complexes reveals association of replication with the viral capsid - Peng, Ke (eLife, 2014)
The steps from HIV-1 cytoplasmic entry until integration of the reverse transcribed genome are currently enigmatic. They occur in ill-defined reverse-transcription- and pre-integration-complexes (RTC, PIC) with various host and viral proteins implicated. In this study, we report quantitative detection of functional RTC/PIC by labeling nascent DNA combined with detection of viral integrase. We show that the viral CA (capsid) protein remains associated with cytoplasmic RTC/PIC but is lost on nuclear PIC in a HeLa-derived cell line. In contrast, nuclear PIC were almost always CA-positive in primary human macrophages, indicating nuclear import of capsids or capsid-like structures. We further show that the CA-targeted inhibitor PF74 exhibits a bimodal mechanism, blocking RTC/PIC association with the host factor CPSF6 and nuclear entry at low, and abrogating reverse transcription at high concentrations. The newly developed system is ideally suited for studying retroviral post-entry events and the roles of host factors including DNA sensors and signaling molecules. DOI: http://dx.doi.org/10.7554/eLife.04114.001